2014
DOI: 10.3855/jidc.4895
|View full text |Cite
|
Sign up to set email alerts
|

One year experience using mycobacterial blood cultures to diagnose tuberculosis in patients with prolonged fever in Vietnam

Abstract: Introduction: To evaluate the use of mycobacterial blood cultures (MBC) in diagnosing tuberculosis (TB) in patients with prolonged fever admitted to a Vietnamese referral hospital. Results: MBCs from 94 patients (66% male; median age 33 years; 75% HIV positive) were evaluated: 14 were mycobacterium positive (all HIV positive), and MBC was the only positive specimen in 9 cases (41%). Three positive cases were identified as Mycobacterium avium and the remaining M. tuberculosis (one case could not be identified).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The time to positivity of mycobacterial blood culture in children with suspected TB in this study was long [median turnaround time (TAT): 25 days], similar to studies in adults. 7,9 Recently, it was found that detection of MTB in blood using GeneXpert MTB/ RIF could produce results within a day. The sensitivity of GeneXpert MTB/RIF was found to be similar to that of mycobacterial blood culture in a study of 104 HIV infected adults, 10 but the high volume of blood used here (20 mL) could be problematic in small children.…”
mentioning
confidence: 99%
“…The time to positivity of mycobacterial blood culture in children with suspected TB in this study was long [median turnaround time (TAT): 25 days], similar to studies in adults. 7,9 Recently, it was found that detection of MTB in blood using GeneXpert MTB/ RIF could produce results within a day. The sensitivity of GeneXpert MTB/RIF was found to be similar to that of mycobacterial blood culture in a study of 104 HIV infected adults, 10 but the high volume of blood used here (20 mL) could be problematic in small children.…”
mentioning
confidence: 99%